Idiopathic CD4+ Lymphocytopenia in Overlap Syndrome (Systemic Sclerosis with Dermatopolimyositis) - Sumartini Dewi; Tasya Aniza Yusuf; Fahrizal Yanuar (Indonesian Journal of Rheumatology, 2021)
Background : Idiopathic CD4 T cell lymphocytopenia (ICL) is a rare syndrome with varied clinical manifestation, characterized with lymphopenia and decreased in CD4 level without HIV infection or other possible cause of immunodeficiency state. Autoimmune diseases might be a clinical manifestation of ICL. However, it is not known whether ICL triggered an autoimmune diseases, or it is a complication of said diseases. Objective : Awareness of ICL in patient with known autoimmune diseases whom admitted to the hospital for severe infection. Methods : This case report showed a 24-years old woman with prolonged fever since 4 moths ago. It was accompanied with oral ulcers, skin rash in face and trunks, and weakness of lower extremities. She was diagnosed with systemic sclerosis since 2016 and routinely came to rheumatology outpatient clinic in Hasan Sadikin Hospital but stopped coming for past 4 months since pandemic. Her current medication was only 4 mg of methylprednisolone. Results : She had high temperature (38.5 degree Celsius) and tachycardia. Physical examination revealed a single lymphadenopathy at neck. Raynaud phenomenon, calcinosis, and sclerodactyly was found in lower extremities. Dermatomyositis was diagnosed based by heliotropic skin rash. Laboratory tests showed leukopenia, absolute lymphocyte count 135.2 cell/mm3, absolute CD4 39/uL, CK level of 3296 and nonreactive anti-HIV. The patient underwent empirical antibiotic treatment, but unfortunately passed away. Conclusion : ICL is a rare case, following an infection, autoimmune diseases, or unspecified malignancy. Clinician’s awareness toward ICL could prevent fatal opportunistic infection which often happens to patients with immunodeficiency state.